The Effect of Investment Opportunities, Accounting Conservatism, and Intellectual Capital on The Cash Dividend Payout Ratio (Studies on Property and Real Estate Sector Companies Registered on The IDX 2018-2020) - sabarudin; Muh. Tahir (Jurnal Penelitian Ekonomi dan Akuntansi (JPENSI), 2023)
The Effect of Investment Opportunities (PI), Accounting Conservatism (KA) and Intellectual Capital (IC) on the Dividend Payout Ratio (DPR) (Case Study of Property and Real Estate Sector Companies Registered on the IDX for the 2018-2020 period). This study aims to determine how much influence Investment Opportunity (PI), Accounting Conservatism (KA) and Intellectual Capital (IC) have on the Dividend Payout Ratio (DPR). This case study aims to examine the effects of three variables, Investment Opportunities (PI), Accounting Conservatism (KA), and Intellectual Capital (IC), on the Dividend Payout Ratio (DPR) for the period spanning 2018-2020. Specifically, it seeks to determine the extent to which these variables influence the DPR. The study population is comprised of companies in the property and real estate sector that are registered on the Indonesia Stock Exchange. In order to obtain a sample, purposive sampling was used to select 12 companies. Data collection was performed through a documentary approach, and multiple regression analysis was employed for analysis. The findings indicate that the investment opportunity variable has a coefficient of 0.452, with a p-value that is greater than the 5% significant level (0.452 > 0.05), indicating that there is no discernible relationship between Investment Opportunities (PI) and the dividend payout ratio (DPR). Upon calculation, the p value was determined to be less than the significant level of ? = 5% or (0.001 < 0.05). This implies that the dividend payout ratio is affected by accounting conservatism. The intellectual capital variable was calculated to be 0.015, with a p-value greater than the significant level of ? = 5% or (0.141 > 0.05), indicating that intellectual capital has no impact on the dividend payout ratio. Additionally, the p-value F test results were determined to be 0.001; the p value being less than the significant level = 5% or (0.001 < 0.05) signifies a positive and significant influence was revealedbetween investment opportunities, accounting conservatism and intellectual capital on the dividend payout ratio.